Topical insulin to treat a conjunctival defect after glaucoma surgery: A case report - Barbara Burgos-Blasco; Sonia N. Yeung; Gavin Docherty; Alfonso Iovieno (American Journal of Ophthalmology Case Reports)
Purpose: Insulin has been postulated as a novel and effective treatment for re-epithelialization of the ocular surface and different pathologies have been suggested as possible indications. Observations: A 69-year-old diabetic male was referred for a left non-healing conjunctival epithelial defect over the superotemporal scleral patch used in the placement of the Ahmed ClearPath. In the left eye, he was on latanoprost/timolol once daily, prednisolone 1 % once daily and tobramycin/dexamethasone ointment at night. Best-corrected visual acuity was 20/20 in the right eye and 20/25 in the left eye. Slit lamp examination of the left eye showed patches of avascular scleral tissue nasally and superiorly, conjunctival and Tenon defect over a thin avascular scleral patch graft. The patient was started on Humulin insulin 1UI/mL 6 times a day and the defect healed after 3 months of treatment. Conclusions and importance: Insulin eye drops may be used in the treatment of chronic conjunctival epithelial defects following implantation of glaucoma drainage devices.